A case study on metacognitive strategies in an engaging multimedia experience - Sheik Said, Normahdiah; Rahman, Saemah; Mohd Yassin, Siti Fatimah (WSEAS Press, 2008)
Knowing strategies on how children think when playing computer games could help educationalist design educational game courseware that engages children to learn. This paper will look at how the children use strategies or lack of it in their thinking to overcome problems when interacting with an engaging multimedia application, The Sims.The Sims, an Edutainment Multimedia CD, was used to discover more about engagement under varying interactive conditions and experiments after the features of what children want in a multimedia design for them were found in this application. A theoretical model “An Engaging Multimedia Design Model” [1] renamed, after an extended research,The NEMD Model (Norma™ Engagement Multimedia Design Model) [3] was developed from this study using this application as the vehicle. This paper is a result of revisiting the recorded engaging experience the children encountered whilst doing the experiments to design, test, redesign and retest till the model gets its present form. A number of metacognitive strategies were sighted in this game play. Relating their thinking to metacognitive strategies will help us design better educational multimedia game courseware for children.